2003
DOI: 10.1261/rna.5820103
|View full text |Cite
|
Sign up to set email alerts
|

B-cell and plasma-cell splicing differences: A potential role in regulated immunoglobulin RNA processing

Abstract: The immunoglobulin µ pre-mRNA is alternatively processed at its 3 end by competing splice and cleavage-polyadenylation reactions to generate mRNAs encoding the membrane-associated or secreted forms of the IgM protein, respectively. The relative use of the competing processing pathways varies during B-lymphocyte development, and it has been established previously that cleavage-polyadenylation activity is higher in plasma cells, which secrete IgM, than in B cells, which produce membraneassociated IgM. To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 48 publications
(80 reference statements)
4
40
1
Order By: Relevance
“…2C) and surface expression (Fig. 2E, top bands) were found, both in bone marrow and spleen cells, as has been described for mRNA products in mouse B cells (37). Figure 2, D and F, illustrate the exon usage of the PCR products, which have been confirmed by cloning and sequencing (supplemental Table I).…”
Section: H Chain Transcripts Are Correctly Splicedsupporting
confidence: 76%
“…2C) and surface expression (Fig. 2E, top bands) were found, both in bone marrow and spleen cells, as has been described for mRNA products in mouse B cells (37). Figure 2, D and F, illustrate the exon usage of the PCR products, which have been confirmed by cloning and sequencing (supplemental Table I).…”
Section: H Chain Transcripts Are Correctly Splicedsupporting
confidence: 76%
“…In polyomavirus, read-through of the late poly(A) site leads to up-regulation of late mRNA levels because the read-through transcripts allow new and productive splicing events to occur. This is reminiscent of the regulation of the production of mRNAs encoding the membrane-associated or secreted forms of the IgM protein, where alternative splicing is masked by efficient polyadenylation or transcription termination (Bruce et al 2003). The difference in the polyoma system is that regulation is achieved by the RNA structure or editing of signals rather than by modulation of polyadenylation or splicing factors.…”
Section: Discussionmentioning
confidence: 99%
“…LPS induction of splenic B-cells increases CstF-64 and introduction of CstF-64 into chicken DT40 B-cells results in Ig secretion (Takagaki, Seipelt et al 1996), see Table 1. Both the Igh 5' splice site in the last sec exon and the sec poly(A) sites are weak and in competition (Peterson and Perry 1989); overall splicing is decreased in plasma cells (Bruce, Dingle et al 2003). A shift in the SR-proteins is seen from the activating type (ASF/SF2) in B-cells to the repression type (SRp20) in plasma cells.…”
Section: Differential Expression Of Factors In a Number Of Pathways Smentioning
confidence: 97%
“…The balance between these has been shown to control many genes, reviewed in (House and Lynch 2008). Changes in the levels of the splicing factors in various B cell types (Bruce, Dingle et al 2003) and during development have been shown to alter splicing patterns (Expert-Bezancon, Sureau et al 2004). For, example, SRp20 plays an important role in alternative splicing of the ED1 exon (de la Mata and Kornblihtt 2006).…”
Section: Splicing Of Igh Rna Is Altered In Plasma Cellsmentioning
confidence: 99%
See 1 more Smart Citation